`(sinx+cosx)^2 = 1+sin2x`

First we will expand the square root.

`==> sin^2 + 2sinxcosx + cos^2 x = 1+ sin2x`

``We know that `sin^2 x + cos^2 x = 1`

`==gt 1 + 2sinxcosx = 1+ 2sinx`

`` Also, we know that: `2sinxcosx = sin2x`

```==gt 1 + sin2x = 1+ 2sinx` ..............q.e.d

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now